1884 Wyo. Terr. Sess. Laws 134, ch. 85, § 28, pt. 1. - (:unkn) unknown (General Publisher, 1884)
[T]o regulate the storage of gun-powder, kerosene and other dangerous material[.]
--
Keywords: GUN POWDER STORAGE